Strategies to overcome myeloid cell induced immune suppression in the tumor microenvironment - Cao, Jennifer; Chow, Lyndah; Dow, Steven (Frontiers in Oncology, 2023)
Cancer progression and metastasis due to tumor immune evasion and drug resistance is strongly associated with immune suppressive cellular responses, particularly in the case of metastatic tumors. The myeloid cell component plays a key role within the tumor microenvironment (TME) and disrupts both adaptive and innate immune cell responses leading to loss of tumor control. Therefore, strategies to eliminate or modulate the myeloid cell compartment of the TME are increasingly attractive to non-specifically increase anti-tumoral immunity and enhance existing immunotherapies. This review covers current strategies targeting myeloid suppressor cells in the TME to enhance anti-tumoral immunity, including strategies that target chemokine receptors to deplete selected immune suppressive myeloid cells and relieve the inhibition imposed on the effector arms of adaptive immunity. Remodeling the TME can in turn improve the activity of other immunotherapies such as checkpoint blockade and adoptive T cell therapies in immunologically “cold” tumors. When possible, in this review, we have provided evidence and outcomes from recent or current clinical trials evaluating the effectiveness of the specific strategies used to target myeloid cells in the TME. The review seeks to provide a broad overview of how myeloid cell targeting can become a key foundational approach to an overall strategy for improving tumor responses to immunotherapy.